High-dose versus Standard-dose Daunorubicin in Induction Chemotherapy for Acute Myeloid Leukemia: A Meta-Analysis - Bibi Kulsoom; Muhammad Nadeem; Hafiza Touseef Sayyar (Journal of University College of Medicine and Dentistry)
Objective: This systematic review and meta-analysis aimed to compare the efficacy and safety of high-dose versus standard-dose daunorubicin in induction therapy for adult acute myeloid leukemia (AML), focusing on complete remission (CR), overall survival (OS), and event-free survival (EFS).